High Order Thinking Skill Questions in Reading Exercises (An Analysis of Reading Exercises in Bright an English Course Book for the Grade IX of Junior High School, Published by Erlangga in 2018 - Nadia Daniati; Fitrawati Fitrawati (Journal of English Language Teaching, 2020)
High Order Thinking Skill (HOTS) is the ability to think in the complex process which useful for transferring the knowledge in real life, thinking critically, and solving the problems. Categories of HOTS level are analyzing, evaluating, and creating.  To assess those abilities, HOTS can we find in reading exercises. This research is aimed to analyze the HOTS questions in reading exercises. This research is descriptive qualitative. Data was collected from Bright an English course book for grade IX of junior high school. This study using indicators in Revised Bloom’s Taxonomy as instrument. The result showed that the the total of HOTS questions is 78 questions or 18,9% from 412 reading questions. The percentage of each HOTS category are 11,9% for analyzing level, 5,8% evaluating level, and 1,2% creating level. Nevertheless, HOTS questions is not the dominant level in this coursebook.  Keywords:  High Order Thinking Skill, reading questions, revised Bloom’taxonomy